Occurrence of subclinical and overt hypothyroidism among chronic kidney disease patients - Jha, Dilip Kumar; Minj, Gregory; Prasad, Umesh; Lahre, Yuvraj; Bodra, Diljeet (International Journal of Research in Medical Sciences, 2020)
Background: Chronic kidney disease (CKD) is one of the vital health problems worldwide leading to increased global morbidity and mortality. Thyroid dysfunction including hypothyroidism, hyperthyroidism and non-thyroidal illness has been reported in CKD patients. This study was conducted to determine the prevalence of subclinical and overt hypothyroidism among chronic kidney disease patients. This study also tried to correlate thyroid function abnormalities with severity of renal failure. Method: In this observational and cross sectional study, 100 patients of CKD who were admitted in Department of Medicine, Rajendra institute of medical sciences, Ranchi were studied for thyroid function abnormalities. Result: This study found that glomerular filtration rate (GFR) is positively correlated with serum T3 and T4 level (i.e. with decreasing renal function both T3 and T4 levels decreased). Serum creatinine levels were negatively correlated with serum T3 and T4 level. Conclusions: From this study it was established that CKD is associated with thyroid dysfunction characterized by low serum fT3 and fT4 with high TSH in some cases.